Implementation of The Policy on Appointment Of Honorary Teacher PPPK and Its Implications on The Quality of Education in The City of Bandung - Fadjar Tri Sakti (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Honorary teachers play a crucial role in Indonesia’s education system; however, their limited employment status and welfare have posed serious challenges to teaching quality. The government addressed this issue through the appointment policy of Government Employees with Work Agreements (PPPK) for honorary teachers, which needs to be analyzed specifically within the context of Bandung City as an educational hub. This study aims to examine the implementation of the PPPK teacher appointment policy and its implications for improving education quality. The theoretical framework includes Edward III’s policy implementation theory, Herzberg’s motivation theory, and Juran’s quality theory. This research employed a descriptive qualitative method using interviews, observations, and document studies, analyzed through Miles & Huberman’s interactive model. The findings indicate that PPPK appointments enhance teacher motivation, stability, and dedication, though challenges remain in terms of administration, budget, and teacher distribution. Therefore, PPPK policy can strategically contribute to strengthening education quality if accompanied by continuous evaluation.